Chuck. The complete fifth and final season [videorecording (Blu-Ray)] - Schwartz, Josh, 1976-; Fedak, Chris; Levi, Zachary, 1980-; Strahovski, Yvonne, 1982-; Gomez, Joshua, 1975-; Lawrence, Mark Christopher, 1964- (Warner Home Video [distributor], 2012)
Chuck is back with new missions, a new business and no Intersect. The stakes are high as Chuck sets out to become a full-fledged spy. Without the CIA as backup, Chuck will have to rely now more than ever on John Casey, Sarah Walker, and a new Intersect, Morgan Guillermo Grimes. Across this thrilling final season, Chuck will find that his wits, his friends, and his family are the only backup he needs.